"I couldn't change the past; the answer wasn't there": A case study on the subjective construction of psychotherapeutic change of a patient with a Borderline Personality Disorder diagnosis and her therapist. (4th July 2019) - Duarte, Javiera; Fischersworring, Martina; Martínez, Claudio; Tomicic, Alemka
Abstract: Background : Qualitative research has provided knowledge about the subjective experiences of therapists and patients regarding the psychotherapy process and its results. Only few studies have attempted to integrate both perspectives, considering the influence of a patient's characteristics and diagnosis in the construction of this experience. Aim : To identify aspects of psychotherapy that contribute to therapeutic change based on the experience of a patient and her therapist, and to construct an integrated comprehension of the change process of a patient with Borderline Personality Disorder. Method : A single case was used to carry out a qualitative analysis of follow-up interviews of the participants of a long-term psychotherapy. Two qualitative approaches were combined into a model entitled "Discovery-Oriented Biographical Analysis" to reconstruct an integrated narrative. Results : This method yielded an integrated narrative organized into four "chapters" that reflect the subjective construction of both the patient's and the therapist's experience of psychotherapy in terms of meaning. Discussion : The understanding of psychotherapy as a multilevel process, in which different themes occur and develop simultaneously, is discussed. From this perspective, psychotherapy can be characterized as a process that involves the recovery of trust in others through corrective emotional experiences and the construction of a shared implicit relational knowledge. Clinical or methodological significance of this article : Research on the subjective experiences of psychotherapy must consider both patient and therapist as privileged but always complementary witnesses of their interaction. In addition, it should be noted that the experience of studying this biographical reconstruction generates a space where research and practice converge. The analysis of participants' narratives provides fascinating windows into their perceptions of psychotherapy and the process of change (Safran, 2013); here, the researcher is not merely a advantaged observer or a good summarizer: He/she has the chance to imbue the psychotherapy with a new meaning by connecting it with a common set of knowledge and a body of socially shared experience.